Professional learning journeys of teacher educators - Butler, Brandon M.; Ritter, Jason K. (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"It is clear that teacher educators have ongoing professional learning and development needs. Chief among these are continuing to learn about content developments and pedagogical practices useful for teaching a range of PK-12 students in varying contexts; developing reflective competencies and sets of practices useful for teaching teacher candidates about teaching; effectively balancing teaching commitments with institutional expectations for scholarship and service; and forging useful understandings of identity across the spectrum of teacher educator responsibility and development over time, including taking on managerial or administrative roles. Working in institutions largely devoid of formal support mechanisms, teacher educators are often left on their own to meet these needs and subsequently must create or seek out opportunities for their ongoing growth. This volume explores in greater depth how exactly teacher educators engage in professional learning and development across their career trajectories. University-based teacher educator learning occurs in a range of settings and across the career span. Contributors to this volume describe university-based teacher educator learning spaces focused on their ongoing professional learning. Such spaces include teacher educator communities of practice, critical friendships, self-study learning groups, faculty learning groups, co-mentoring, and institutionally sponsored professional learning spaces"-- Provided by publisher.
Keywords: Teacher educators -- In-service training -- United States.; Teacher educators -- Professional relationships -- United States.; Communities of practice -- United States.; Teachers -- Training of -- United States.; Education -- Study and teaching (Higher) -- United States.; Education -- Professional Development.; Teacher training.; elektronické knihy; electronic books